A Review on the Treatments for Monocular Visual Impairment for the Development of a Visual Aid - Ravindran, Nirvenesh; Mohamed, Hassan (International Journal of Engineering and Technology, 2018)
Amblyopia is the most commonly found monocular visual impairment in the world. This paper presents an initial investigation into developing a visual aid for monocular visual impaired patients. The investigations conducted in this paper include those from direct interviews from consultant ophthalmologist. Investigations include reviewing the principle required to be embedded into the visual aid such as the distance and depth perception. Stereoscopic cameras and algorithms are also further discussed to interlink with the concepts of depth perception. Monocular visual impairment can most of the time be caused by medical conditions like amblyopia or glaucoma, and rarely caused by accidents and external factors. Thus, existing treatments for amblyopia, the effectiveness and challenges of the treatment are also clearly investigated and scrutinized in this paper. Some of the existing treatments include refractive therapy, occlusion therapy, atropine injections, perceptual learning, pharmacological treatment and acupuncture. This study has provided a clear insight into the requirements of developing a visual aid, thus further addressing the challenges faced by the treatments in this impairment.
Keywords: Monocular; Visual; Impairment; Aid; Amblyopia